1994
DOI: 10.1104/pp.105.2.563
|View full text |Cite
|
Sign up to set email alerts
|

The rolB Gene of Agrobacterium rhizogenes Does Not Increase the Auxin Sensitivity of Tobacco Protoplasts by Modifying the Intracellular Auxin Concentration

Abstract: Phenotypical alterations observed in rolB-transformed plants have been proposed to result from a rise in intracellular free auxin due to a RolB-catalyzed hydrolysis of auxin conjugates (J.J. Estruch, J. Schell, A. Spena [1991] EMBO J 10: 3125-3128). We have investigated this hypothesis in detail using tobacco (Nicofiana tabacum) mesophyll protoplasts isolated from plants transformed with the rolB gene under the control of its own promoter (BBCUS 6 clone) or the cauliflower mosaic virus 35s promoter (CaMVBT 3 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 16 publications
0
36
1
1
Order By: Relevance
“…Protoplasts derived from such tobacco plants are 105-fold more sensitive to auxin than protoplasts of wild-type plants . However, neither free nor conjugated IAA levels were modified in P35S-rolB-transformed tobacco plants or protoplasts (Nilsson et al, 1993;Schmülling et al, 1993;Delbarre et al, 1994). It is therefore unlikely that the surl mutant is affected in its ability to sense auxin.…”
Section: Linkage Analysismentioning
confidence: 94%
“…Protoplasts derived from such tobacco plants are 105-fold more sensitive to auxin than protoplasts of wild-type plants . However, neither free nor conjugated IAA levels were modified in P35S-rolB-transformed tobacco plants or protoplasts (Nilsson et al, 1993;Schmülling et al, 1993;Delbarre et al, 1994). It is therefore unlikely that the surl mutant is affected in its ability to sense auxin.…”
Section: Linkage Analysismentioning
confidence: 94%
“…Subsequent analyses have demonstrated that, unlike the original hypothesis suggested, rolB activity does not interfere with the endogenous auxin metabolism (Delbarre et al, 1994;Nilsson et al, 1993a;SchmLilling et al, 1993a). In a recent publication Fillipini et al (1996) reported that the rolB enzyme also has an in vitro tyrosine phosphatase activity.…”
Section: Introductionmentioning
confidence: 99%
“…This pattern resembled that of stem slices inoculated with A. rhizogenes. The results also correspond with the increased root formation on explants of kiwi transformed with ArolA+BrolB+CrolC [20]. It suggests that rolA and rolC enhanced the promotive effect of rolB on rooting.…”
Section: Discussionmentioning
confidence: 49%